Islamic Law And Gendered Inheritance: An-Taradhin as Breakthrough for Women’s Rights Disputes in Java, Bali, and Sumatra - Sugianto, Hendi; Fawaid, Achmad; Baharun, Hasan; Yarun, Ayuningtias (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
The Indonesian government provides legal protection for women, but they face ongoing challenges in preserving land ownership in various regions. This article aims to explore three main points: (a) women’s contested land ownership and inheritance rights in Java, Bali, and Sumatra, (b) the successful breakthroughs in the application of Islamic law in addressing these contestations in other regions, and (c) the idea of ​​an-taradhin as a practical solution to these disputes. This study employs a qualitative empirical legal research approach, combining documentary analysis of statutory frameworks and Islamic legal sources with field interviews with several stakeholders (ranging from PPAT to NGOs). The empirical data were gathered through fieldwork in selected rural communities across Java, Bali, and Sumatra. This dual approach integrates normative legal analysis with empirical findings to offer a contextualized understanding of the application of Islamic law. This study reveals that Islamic laaw, when contextualized with local customs, offers a viable framework to overcome cultural and legal barriers. Notably, the principle of an-taradhin demonstrates potential to uncover the issue of women’s land and inheritance rights amidst legal and customary conflicts in Indonesia. This study also recommends breakthroughs by providing some lessons from other cases of implementing an-taradhin in various regions (such as in the Sundanese, Sampang, and Yoruba communities). This study contributes primarily to Islamic legal studies with significant implications for customary law reform and gender justice, by proposing the integration of Sharia-based principles such as maslahah and an-taradhin within pluralistic legal systems.